2001
DOI: 10.1211/0022357011777846
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro activity of S. lavandulaefolia (Spanish sage) relevant to treatment of Alzheimer's disease

Abstract: Salvia lavandulaefolia Vahl. (Spanish sage) essential oil and individual monoterpenoid constituents have been shown to inhibit the enzyme acetylcholinesterase in-vitro and in-vivo. This activity is relevant to the treatment of Alzheimer's disease, since anticholinesterase drugs are currently the only drugs available to treat Alzheimer's disease. Other activities relevant to Alzheimer's disease include antioxidant, anti-inflammatory and estrogenic effects. Results of in-vitro tests for these activities are repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
91
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(94 citation statements)
references
References 43 publications
3
91
0
Order By: Relevance
“…This suggests that treatments that predominantly inhibit BuChE (as here) may prove particularly efficacious in the augmentation of ACh levels. Added to this, the mood improvements seen here and elsewhere in humans, and other key properties that may slow the pathogenesis of disease or natural decline (eg antioxidant, anti-inflammatory, oestrogenic (Perry et al, 2001), suggest that sage may well confer a number of benefits above and beyond current treatments. Preliminary support for this is provided by the two studies that have assessed the effects of sage species in AD.…”
Section: Discussionmentioning
confidence: 93%
“…This suggests that treatments that predominantly inhibit BuChE (as here) may prove particularly efficacious in the augmentation of ACh levels. Added to this, the mood improvements seen here and elsewhere in humans, and other key properties that may slow the pathogenesis of disease or natural decline (eg antioxidant, anti-inflammatory, oestrogenic (Perry et al, 2001), suggest that sage may well confer a number of benefits above and beyond current treatments. Preliminary support for this is provided by the two studies that have assessed the effects of sage species in AD.…”
Section: Discussionmentioning
confidence: 93%
“…Inhibition of acetylcholinesterase (AChE) was assessed by a modified colorimetric method of Ellman (Perry et al 2000). The AChE activity was determined in a reaction mixture containing 200 μL of brain AChE solution (EC 3.1.1.7) in 0.1 M phosphate buffer, pH 8.0, 100 μL of a solution of 5,5′-dithio-bis(2-nitrobenzoic) acid (DTNB 3.3 mM in 0.1 M phosphate buffered solution, pH 7.0, containing NaHCO 3 6 mM), vegetable extracts (0-100 μl) and 500 μL of phosphate buffer, pH 8.0.…”
Section: Acetylcholinesterase (Ache) and Butyrylcholinesterase (Bche)mentioning
confidence: 99%
“…Previous studies demonstrated that many Salvia species and their isolated constituents possess antioxidant activity (Zupko et al 2001), antiinflammatory activity (Howes et al 2003) and cholinesterase inhibition effect (Perry et al 2001.…”
mentioning
confidence: 99%